Monitoring of Programmed Cell Death Ligand-1 Blockade Using FDG PET/CT for Microsatellite Instability-High Metastatic Breast Cancer. (March 2022) - Kawamata, Ayumi; Sasada, Shinsuke; Emi, Akiko; Masumoto, Norio; Kadoya, Takayuki
Abstract : Abstract: Microsatellite instability-high/mismatch repair deficiency is one of biomarkers predicting the response to pembrolizumab, an immune checkpoint inhibitor for metastatic solid tumors. A 44-year-old woman with stage IIIC right breast cancer was treated with mastectomy and axillary node dissection after primary systemic chemotherapy followed by radiation, chemotherapy, and hormonal therapy. Eighteen months after surgery, recurrent diseases were revealed and refractory to multiple treatments. The recurrent site biopsy showed microsatellite instability-high, and programmed cell death ligand-1 inhibitor pembrolizumab was administrated. FDG PET/CT showed complete metabolic response over 12 months and is useful to monitor the response of active immunotherapy.